The Impact of Destination Exposure in Reality Shows on Destination Image, Familiarity, and Travel Intention - Mege, Stacia Reviany; Aruan, Daniel Tumpal H (ASEAN Marketing Journal, 2021)
The increasing popularity of reality shows renders them as potential media for tourism promotion. However, there is limited research regarding the impact of destination exposure in reality shows. This study aimed to investigate the impact of destination exposure in television reality shows on destination image, familiarity, and travel intention. To test the hypotheses, a within subject experiment was conducted. A worldwide popular reality show, The Amazing Race, was used as a stimulus for the participants. The results revealed that, in general, both cognitive and affective destination im- ages were rated higher after watching the reality show. Furthermore, familiarity with the destination and travel intention to the destination increased after watching the destination in the reality show. The result of this study will be useful for destination marketing organization and the government to explore alternative promotional media and aid the promotion of tourism destination.